Pengembangan Media Pembelajaran Berbentuk komik Pada Materi Sistem Saraf Pada Manusia Dalam Mata Pelajaran Biologi Untuk SMP - Mona Sari, Rika; Risdawati, M.Si., Dra. Hj. Renny; Widiana, Rina (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Instructional media can be defined as the means for facilitating the teaching and learning activities. They can be facilities which provides the students with visual experience to motivate them to learn, explain and simplify the abstract complicated concepts into simpler, more concrete Â and more understandable ones. They generate the studentsâ curiosity, motivate and stimulate them to learn. The media used previously, however, had made the students got bored so that they were not interested in paying attention to the teachers explaining the lesson in front of the class. To deal with this problem, comic instructional media for teaching human neural system whichÂ was Â intended Â to Â motivate the Â students Â to Â learnÂ and Â to Â improve Â their Â learning Â interest Â was developed. This research was aimed at revealing the validity and the practicality of the instructional media. This was a developmental research which used 4-D models that consisted of four developmental stages including defining, designing, developing and disseminating. For the limitation of time and budget, in this research, however, disseminating phase was excluded. The media developed were validated by t wo lecturers and two teachers of SMP Pertiwi Siteba Padang. The practicality of the media was seen from the responses given by two teachers and 25 students in class IX-1 of Junior High School. The result of data analysis indicated that the comic media developed was valid in which the validity value was 78,33%. The validity was viewed from didactic, construction and technical variables. The result of the practicality test from the teachers showed that the comic media was practical in which the practicality value was 78,55%, while the result of the practicality test from the students indicated that the comic media was very practical in which the practicality value was 88,05%. The practicality was viewed from the studentsâ interests, the pictures displayed in t he media, the process of using the media, material and conceptual understanding, time efficiency and evaluation. Based on these results, it was concluded that the comic instructional media developed for teaching human neural system had been valid and practical.